2009
DOI: 10.2478/s11756-009-0156-x
|View full text |Cite
|
Sign up to set email alerts
|

Nutlet surface micromorphology of Turkish Satureja (Lamiaceae)

Abstract: There are some taxonomic uncertainties within the Turkish members of Satureja. It is extremely difficult to distinguish some of Satureja species because of their great morphological similarity. They are represented by fifteen species in Turkey. In this study, the nutlet surface features of species were examined using both stereoscopic and scanning electron microscopy (SEM). The investigated species can be divided into two main types, the more or less smooth and the sculptured, and four subtypes, undulate-retic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 5 publications
(8 reference statements)
4
40
0
Order By: Relevance
“…In dimensions' measurements, obtained results showed fairly range of variations in nutlets size, so, the color, shape, and size can be of little taxonomic important. Similar conclusions have also been given by Karakish (1993), Hamed and Mourad (1994), Shaheen (2002), Kaya and Dirmencl (2008), Budantsev (1993), and Kasem (2016 …”
Section: 1) Isoenzymessupporting
confidence: 83%
“…In dimensions' measurements, obtained results showed fairly range of variations in nutlets size, so, the color, shape, and size can be of little taxonomic important. Similar conclusions have also been given by Karakish (1993), Hamed and Mourad (1994), Shaheen (2002), Kaya and Dirmencl (2008), Budantsev (1993), and Kasem (2016 …”
Section: 1) Isoenzymessupporting
confidence: 83%
“…al. 2010;Celep et al 2012;Kaya & Dirmenci 2012;De Paula et al 2013;Lantieri et al 2013). Salimpour et al (2007) examined seeds in Trifolium L. and concluded that seed A c c e p t e d M a n u s c r i p t shape, size, sculpturing pattern and hilum shape can be used as taxonomic markers within the section Lotoidea Crantz.…”
Section: Have Been Demonstrated Thatmentioning
confidence: 99%
“…Species of the Salvia genus are used in traditional medicines all around the world, as they possess antibacterial, antioxidative, antidiabetic and antitumor properties (Ulubelen 2003;Şenol et al 2010). The number of morphological and medicinal plant studies has increased in recent years (Çakılcıoğlu & Türkoğlu, 2007;Serdar et al 2007;Terzioğlu et al 2007;Yaman 2009;Brus et al 2011;Khatun et al 2011Khatun et al , 2012Kaya & Dirmenci 2012;Corp & Pendry 2013;Gottschlich et al 2013;Guarino et al 2013;Sciandrello et al 2013;Selvi et al 2013Selvi et al , 2015Hayta et al 2014Hayta et al , 2015Ferrauto et al 2015).…”
Section: Introductionmentioning
confidence: 99%